SUCCESSFUL MANAGEMENT OF SHARP ABDOMINAL TRAUMA WITH DIAGNOSTIC LAPAROSCOPY AT DR. ZAINOEL ABIDIN ACEH HOSPITAL - Khalikul Razi; Muhammad Azmi Fanany; Muhammad Yusuf; Ferry Erdani; Muslim (Universitas Batam, 2024)
Abdominal trauma is injury that occurs to organs in the abdomen, such as the stomach, intestines, liver, spleen, pancreas, bile and kidneys, damage to the structures located between the diaphragm and pelvis. Abdominal trauma is divided into two types, namely blunt abdominal trauma and stab abdominal trauma. Injuries to the intestines and liver are the most common in penetrating trauma to the abdomen. Case report: a 35 year-old man came to the Emergency Room at the Dr. Zainoel Abidin Regional General Hospital in Banda Aceh with the main complaint of a wooden stab wound (foreign body) on the right side of the abdomen which had penetrated to the back. The patient underwent diagnostic laparoscopy, it was found that a piece of wood (foreign body) was stuck in the liver segment V-VI which had penetrated to the right flank and a hematoma was found around the body and about 100 cc of hemorrhagic fluid originating from the liver due to contact with wood friction but the bleeding was not active. Based on the primary and secondary survey evaluations, the hemodynamic condition was stable. In the evaluation, there were no intra-abdominal organ injury. Extraction of the foreign body wood could be performed well after identification of being free from intra-abdominal organ injury. Conclusion: Abdominal trauma is an injury that occurs to organs in the stomach, such as the stomach, intestines, liver, spleen, pancreas, gallbladder, and kidneys. In this case, it was a penetrating stab wound with stable hemodynamics and no small intestine and omental protruding from the stomach, so this patient underwent diagnostic laparoscopic surgery. The operation with diagnostic laparoscopic in this case was successful and minimally invasive.